The potential role of sucrose transport gene expression in the photosynthetic and yield response of rice cultivars to future CO2 concentration. Issue 1 (8th May 2019) - Zhang, Jishuang; Li, Danfeng; Xu, Xi; Ziska, Lewis H.; Zhu, Jianguo; Liu, Gang; Zhu, Chunwu
Abstract : The metabolic basis for observed differences in the yield response of rice to projected carbon dioxide concentrations (CO2 ) is unclear. In this study, three rice cultivars, differing in their yield response to elevated CO2, were grown under ambient and elevated CO2 conditions, using the free‐air CO2 enrichment technology. Flag leaves of rice were used to determine (1) if manipulative increases in sink strength decreased the soluble sucrose concentration for the 'weak' responders and (2), whether the genetic expression of sucrose transporters OsSUT1 and OsSUT2 was associated with an accumulation of soluble sugars and the maintenance of photosynthetic capacity. For the cultivars that showed a weak response to additional CO2, photosynthetic capacity declined under elevated CO2 and was associated with an accumulation of soluble sugars. For these cultivars, increasing sink relative to source strength did not increase photosynthesis and no change in OsSUT1 or OsSUT2 expression was observed. In contrast, the 'strong' response cultivar did not show an increase in soluble sugars or a decline in photosynthesis but demonstrated significant increases in OsSUT1 and OsSUT2 expression at elevated CO2 . Overall, these data suggest that the expression of the sucrose transport genes OsSUT1 and OsSUT2 may be associated with the maintenance of photosynthetic capacity of the flag leaf during grain fill; and, potentially, greater yield response of rice as atmospheric CO2 increases.